Plasma phospholipids profiling changes were associated with the therapeutic response to Roxadustat in peritoneal dialysis patients - Yang, Ya-Hui; Saimaiti, Yishakejiang; Zhao, Yang; Tang, Wen (Frontiers in Physiology, 2023)
Background: Elevated Phospholipids (PLs) and sphingolipid (SM) metabolism is connected with poor clinical status and adverse outcome of end-stage kidney disease patients undergoing peritoneal dialysis (PD). Studies have suggested that the use of hypoxia-inducible factor prolyl hydroxylase inhibitor (HIF-PHI)(Roxadustat) is associated with altered lipid metabolism. Observing on how PLs and SMs changes after the HIF-PHD treatment in PD patients may help understand the possible effect of HIF-PHI on PD patients besides correcting of anemia.Roxadustat for over 3 months were included. Phospholipid and sphingolipid metabolism were measured before and after treatment.Results: 25 PD patients were included. Overall, phospholipid and sphingolipid metabolism showed a decreasing trend after HIF-PHI treatment. Levels of LysoPC (20:0), 1,2-dilinoleoyl-sn-glycero-3-phosphocholine[CisPC (DLPC)(18:2)], lysophosphatidylethanolamine (LysoPE) (14:0), and sphingomyelin (d18:1/17:0) (17:0) were significantly decreased (all p<0.05). Further regression analyses confirmed the significant relationship between the increased rate of hemoglobin levels and the decrease in egg lyso PC: phosphatidylethanolamines(PE) (16:0-18:1), PE (16:0-18:2), PE (16:0-22:6), PE (18:0-20:4), PE (18:0-18:2), LysoPE (18:0), LysoPE (18:1), and phosphatidylcholine(PC) (18:1-18:0).This study demonstrated that phospholipid and sphingolipid metabolism decreased after administration of HIF-PHI and was associated with improvement of anemia.Phospholipids profiling changes and Roxadustat treatment